Serpentinization in Jezero crater: Comparing SuperCam Mars data to terrestrial serpentinites - J.M. Comellas; S.K. Sharma; P.J. Gasda; A. Cousin; A. Essunfeld; P. Fryer; L.E. Mayhew; L. Sun; A.J. Brown; T.E. Acosta-Maeda; E. Dehouck; M. Veneranda; et al. (Icarus, 2026)

Thermal history and behavioural plasticity shape reef fish tolerance to marine heatwaves - Angus Mitchell; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Guinther Mitushasi; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Coral Reefs, 2026)
Marine heatwaves are becoming more frequent and intense, driving mass fish mortalities and reshaping marine ecosystems, yet the capacity of fishes to tolerate heatwaves remains unclear. We quantified physiological condition and behavioural responses of juvenile warm-water ( Abudefduf vaigiensis ) and cool-water ( Microcanthus strigatus ) fishes from three natural climate analogues—an ambient temperate reef, an ocean warming analogue, and a combined warming and extreme acidification analogue—before and during the 2023 global marine heatwave, and under a + 3 °C simulated heatwave in the laboratory. In the laboratory, warm-water fish from the warm reef began the experiment in leaner condition than cool reef fish but increased their bite rates under heatwave conditions, compensating for elevated metabolic demand and maintaining body condition. Cool-water fish showed no behavioural adjustment to the heatwave, and body condition diverged by reef origin: cool reef fish lost weight across all treatments while warm- and extreme-origin fish maintained condition, suggesting tolerance was conferred by prior thermal history rather than acute behavioural responses. In the field, warm-water fish were leaner and had lower protein content during the 2023 heatwave than before it, while cool-water fish from the extreme reef had lower body condition than those from the cool reef prior to the heatwave. Our findings suggest that behavioural plasticity can facilitate warm-water fish tolerance to heatwaves at their cold leading edges, while thermal history supports heatwave tolerance in cool-water fish within their core ranges. Populations inhabiting naturally extreme climate analogues may therefore harbour pre-adapted, climate-resilient fish in a future ocean.

Lowland tropical forests remain a methane sink under warming and long-term hurricane disturbance recovery - Gabriele Larocca Conte; Lucia Zuvela; Rachel Cruz-Pérez; Tatiana Barreto-Vélez; Nibia Becerra-Santillan; Sophia F. Campbell; Hieu P. Chu; Trung Dam; Iana F. Grullón-Penkova; Miriam Kleit; Deyaneira A. Ortiz-Iglesias; Laura C. Rubio-Lebrón; et al. (Agricultural and Forest Meteorology, 2026)

When Scientific Reassessment Fails Citizen Science. Comment on Soldo, A. When Citizen Science Becomes Speculation: Evaluating the Reliability of Lamnid Shark Identification from Photographic Records in the Mediterranean. J. Mar. Sci. Eng. 2026, 14, 173 - Patrick L. Jambura; Julia Türtscher; Joshua K. Moyer; Kenshu Shimada; Ilija Ćetković; Branko Dragičević; Pero Ugarković; Mišo Pavičić; Phillip C. Sternes; Simone Niedermüller; Jacopo Bernardi; Matteo Barbato; et al. (Journal of Marine Science and Engineering, 2026)
Soldo [...]

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Marine invertebrates and fishes exhibit inconsistent body size responses to ocean acidification - Mary E. Hart; Sean D. Connell; Angus Mitchell; Ben P. Harvey; Sylvain Agostini; Joshua M. Heitzman; Ivan Nagelkerken (Limnology and Oceanography, 2026)
Body size is a fundamental characteristic of all living organisms that determines physiological functions and life‐history traits. Ecological theory predicts that ocean acidification can cause body size reductions, confirmed by several studies reporting miniaturization in ectotherms. Based on this prediction, we would expect a broad suite of species to show similar plastic body‐size responses to elevated CO 2 . Using four natural climate change analogues of ocean acidification across the northern and southern hemispheres, we quantified body size alterations across 18 marine invertebrate and fish taxa to test for climate‐driven miniaturization. Only three species consistently showed body‐size reductions under ocean acidification: one urchin and two fish species. In contrast, 15 other species, ranging from highly calcified to non‐calcified, displayed unchanged or increased body sizes or inconsistent miniaturization. If body‐size miniaturization responses were consistently reproducible across taxa we would have observed it more frequently, suggesting that species responses to ocean acidification are more variable than previously thought and likely vary depending on a species' physiology and life history. Thus, rather than entire communities undergoing miniaturization, species are likely to display a spectrum of responses, with some exhibiting size reductions, others demonstrating physiological resistance to elevated CO 2 , and others potentially benefiting from the indirect effects of ocean acidification.

Shear Stress Initiates Endothelial-to-Mesenchymal Transition in Endocardial Endothelial Cells - Kathleen N. Brown; Hong Kim T. Phan; Tasneem Mustafa; Elysa Jui; Fariha N. Ahmad; Ravi K. Birla; Philippe Sucosky; Jennifer P. Connell; Sundeep G. Keswani; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2026)
Discrete subaortic stenosis (DSS) is a congenital heart disease in which a fibrotic membrane forms below the aortic valve; the underlying cellular mechanisms are currently unknown. Since an elevated pressure gradient in the left ventricular outflow tract (LVOT) is a distinguishing feature of DSS, it is hypothesized that the membrane formation is caused by elevated wall shear stress applied to the endocardial endothelial cells (EECs) that line the LVOT, triggering fibrosis. To correlate shear stress to an EEC fibrotic phenotype, we applied fluid shear stress to EECs at physiological and pathological shear rates using a cone-and-plate device, designed to recapitulate physiological wall shear stress in a controlled in vitro environment. Controlled shear stress regimes were applied to EECs to replicate the conditions observed in DSS patients. We found that elevated shear stress triggered EEC alignment as well as endothelial-to-mesenchymal transformation (EndMT) signaling pathways driven by upregulation of SNAI1 gene expression. The EECs were then treated with a small molecule inhibitor of Snail1 protein, CYD19, to attempt to attenuate EndMT signaling, and subsequently subjected to pathological shear stress. The Snail1 inhibitor did downregulate selected markers of EndMT signaling, although only transiently. Interestingly, the application of shear stress had a greater effect on the EEC gene and protein expression than did the Snail1 inhibition. This investigation of EEC response to shear stress reveals the pronounced and complex effect of this mechanical stimulation on the EEC phenotype. Further study should reveal the mechanisms that drive fibrosis and the formation of the DSS membrane.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Marine Heatwaves, Ocean Warming and Acidification Reshape Reef Fish Gut Microbiomes - Angus Mitchell; Chloe Hayes; Callum J. Hudson; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Molecular Ecology, 2026)
Extreme climatic events and gradual climate change are increasingly anticipated to interact and reshape ecological communities. However, the combined effects of ocean warming, acidification and marine heatwaves on host‐associated microbial communities and their potential role in host adaptation remain poorly understood. Here, we assessed shifts in gut microbiome communities and their associations with physiological performance in one tropical ( Abudefduf vaigiensis ) and one subtropical ( Microcanthus strigatus ) reef fish species, across three temperate reefs representing natural analogues of climate change: a present‐day baseline (‘cool reef’), a chronically warmed reef (‘warm reef’) and a reef experiencing combined warming and extreme acidification (‘extreme reef’). We also examined gut microbiome changes in A. vaigiensis before and during a severe marine heatwave. A. vaigiensis had lower gut microbiome evenness and diversity at the warm (43% and 44% decrease, respectively) and extreme (38% and 31% decrease) reefs compared to the cool reef, and its gut microbiome community shifted at the extreme reef with a 122% increase in abundance of opportunistic bacteria Vibrio . A. vaigiensis also had lower gut microbiome richness at the warm (42% decrease) and extreme (52% decrease) reefs during the heatwave compared to pre‐heatwave individuals. In contrast, M. strigatus showed higher microbiome evenness (99% increase) and diversity (98% increase) at the warm reef compared to the cool reef; however, these gains were lost at the extreme reef, with microbiome diversity and evenness returning to cool reef levels. Microbiome changes in both species were generally not associated with their physiological performance (protein content, oxidative stress, antioxidant capacity or body condition). Our findings suggest that marine heatwaves, ocean warming and acidification can reshape reef fish gut microbiomes, driving simplification in Abudefduf vaigiensis but distinct restructuring in Microcanthus strigatus . We conclude that climate‐driven microbiome reshuffling may alter host–microbiome relationships and functions in fishes in a future ocean.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Range‐extending fish become competitive dominants under ocean warming but not heatwaves or acidification - Angus Mitchell; Ericka O. C. Coni; Sean D. Connell; David J. Booth; Ben P. Harvey; Sylvain Agostini; Timothy Ravasi; Ivan Nagelkerken (Ecology, 2026)
Ocean warming is driving species range extensions into cooler regions. The direct physiological influence of warming on species performance can accelerate such extensions into novel ecosystems; however, indirect effects of invader–resident interactions in cooler regions may counter these positive effects. Here, we examined the foraging performance and densities of competing warm‐water and cool‐water fishes across a latitudinal temperature gradient spanning 1500 km from tropical to temperate reefs subjected to rapid ocean warming in the southern hemisphere, and across natural analogs of temperate, tropicalized, and acidified reef localities in the northern hemisphere, and during a severe marine heatwave at a temperate reef. While current levels of ocean warming have allowed the warm‐water fish to extend their ranges into temperate ecosystems at both hemispheres, their foraging performance was reduced at both the cold‐ and warm‐temperate reefs compared to the (sub)tropical reefs. However, at the (warmer) tropicalized reef, the warm‐water fish had higher foraging performance and maintained densities, even under extreme pH reduction, compared to the temperate reef. In contrast, the cool‐water species struggled at the warmer tropicalized and extreme reefs with reduced foraging performance and lower population densities compared to the temperate reef. Contrastingly, the severe heatwave experienced at the temperate reef did not alter the foraging behaviors of either species. We suggest that ocean warming boosts the foraging performance of the range‐extending warm‐water fish and impairs that of their cool‐water competitor at temperate reefs, irrespective of acidification and heatwaves, leading to a shift in dominance hierarchies on temperate reefs. We conclude that warming‐driven increases in foraging performance of the warm‐water species may alleviate foraging limitations and enhance its establishment at its leading range edges under climate change, to the detriment of its cool‐water competitors.

Enhancing soil health and phosphorus use efficiency with modified biochar amendment - Juan P. Frene; Nitesh Kasera; Deb P. Jaisi; Sundar Sapkota; David W. O'Connell; Suzanne Higgins; Sushil Adhikari; Rajan Ghimire (Science of The Total Environment, 2025)

Spectral reflectance (0.35–2.50 μm) properties of minerals and organic-bearing compounds exposed to current Martian surface conditions - S.A. Connell; D.M. Applin; E.A. Cloutis; J.T. Poitras; D.T. Dixon; S.A. Mertzman; P. Mann; C. Royer; T. Fornaro; A. Broz; R.C. Wiens (Icarus, 2025)

Benthic community change and stress-tolerant coral at a high-latitude coral community in the northwestern Gulf of Mexico - Marissa F. Nuttall; Kelly O’Connell; Ryan J. Eckert; Emma L. Hickerson; Olivia Eisenbach; Donavon French; Jennifer L. DeBose; Michelle Johnston; G. P. Schmahl (Coral Reefs, 2025)

Correction to: A global review of white shark (Carcharodon carcharias) parturition - Craig P. O’Connell; Jon F. Dodd; Julia Crews; Juliet Gressle; Breanna Racicot; Steven Sitzer; Timothy Lis; Gregory B. Skomal (Reviews in Fish Biology and Fisheries, 2025)

Real-time amplification and high resolution melt analysis on a rapid microfluidic instrument - Renna L. Nouwairi; Killian C. O'Connell; Rachelle A. Turiello; Larissa L. Cunha; Leah M. Gunnoe; Allison C. Burton; Ryan M. Gibiser; Margaret E. Straub; James P. Landers (Analytica Chimica Acta, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Environmental risk factors for all-cause dementia, Alzheimer's disease dementia, vascular dementia, and mild cognitive impairment: An umbrella review and meta-analysis - Aaron Jones; Muhammad Usman Ali; Alexandra Mayhew; Komal Aryal; Rebecca H. Correia; Darly Dash; Derek R. Manis; Atiya Rehman; Megan E. O'Connell; Vanessa Taler; Andrew P. Costa; David B. Hogan; et al. (Environmental Research, 2025)

A systematic meta-analysis of the efficacy of treatments for a global honey bee pathogen - the Varroa mite - Darren P. O'Connell; Kevin Healy; Jack Wilton; Cristina Botías; Julia C. Jones (Science of The Total Environment, 2025)

Cerebellar Ataxia, Neuropathy, and Vestibular Areflexia as a Presentation of a Novel DNMT1 Mutation - Jake Sossamon; Patrick O’Connell; David P. W. Rastall (The Cerebellum, 2025)

Shear Stress Induces a Time-Dependent Inflammatory Response in Human Monocyte-Derived Macrophages - Elysa Jui; Griffin Kingsley; Hong Kim T. Phan; Kavya L. Singampalli; Ravi K. Birla; Jennifer P. Connell; Sundeep G. Keswani; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A global review of white shark (Carcharodon carcharias) parturition - Craig P. O’Connell; Jon F. Dodd; Julia Crews; Juliet Gressle; Breanna Racicot; Steven Sitzer; Timothy Lis; Gregory B. Skomal (Reviews in Fish Biology and Fisheries, 2024)

Rolling with the punches—How competition shapes the morphology of small passerines on small islands - David J. Kelly; Darren P. O'Connell; Fionn Ó Marcaigh; Seán B. A. Kelly; Adi Karya; Kangkuso Analuddin; Nicola Marples (Journal of Biogeography, 2024)
Aim Wallacea is a global biodiversity hotspot and Sulawesi is the largest island in this region, notable for a high proportion of endemic species. The Wakatobi archipelago, off the southeastern peninsular arm of Sulawesi, is home to several endemic bird species. Although islands are known to influence the morphology of their resident species, competitive interactions also exert strong influences on morphology. Here, we consider the contributions of both islands and competitors on two morphological traits of two bird species in a small passerine guild found on the Wakatobi islands. Location Wakatobi archipelago, Sulawesi Tenggara, Indonesia. Taxon Wakatobi White‐eye ( Zosterops flavissimus ) and Wakatobi Sunbird ( Cinnyris infrenatus ). Methods Working with morphological measures (from netting studies), population density metrics (from transect surveys) and fundamental data from islands (area, distance from mainland and elevation), we investigated (by means of multiple linear regression) which terms best explained variation in the body size and bill size of two small passerine birds endemic to the Wakatobi islands. Results Both island metrics and competitor presence/density were useful in describing the variation in body size of both bird species. However, only competitor presence/density was useful in describing variation in bill size of the birds. The best models describing variation in these traits included terms representing both interspecific and intraspecific competition. Main Conclusions Our findings indicate that simple island metrics may be useful in predicting some of the variation in some functional traits of island species. However, in this example, simple island metrics were insufficient to explain the full variation in body size of endemic birds across the Wakatobi archipelago and were of no use in predicting the variation in their bill size. As bill morphology frequently dictates diet and feeding niche, it is a trait which may determine population divergence and speciation. If simple island metrics fail to describe such diversification, it is surely important to capture that information in other ways.

Increasing temperature and time in glasshouses increases honey bee activity and affects internal brood conditions - Darren P. O'Connell; Bronte M. Baker; David Atauri; Julia C. Jones (Journal of Insect Physiology, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Quantification and classification of a giant fluvial-distributive system - the Triassic Mungaroo Formation, NWS, Australia - T.H.D. Payenberg; B.J. Willis; P. Sixsmith; S.D. Connell; A. Powell; K.T. Milliken; H.W. Posamentier; A. Allgoewer; E. Meyers; T. Marsh; M.D. Sullivan; S.C. Lang; et al. (Earth-Science Reviews, 2024)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Barriers to chimpanzee gene flow at the south‐east edge of their distribution - Noémie Bonnin; Alex K. Piel; Richard P. Brown; Yingying Li; Andrew Jesse Connell; Alexa N. Avitto; Jean P. Boubli; Adrienne Chitayat; Jasmin Giles; Madhurima S. Gundlapally; Iddi Lipende; Elizabeth V. Lonsdorf; et al. (Molecular Ecology, 2023)
Populations on the edge of a species' distribution may represent an important source of adaptive diversity, yet these populations tend to be more fragmented and are more likely to be geographically isolated. Lack of genetic exchanges between such populations, due to barriers to animal movement, can not only compromise adaptive potential but also lead to the fixation of deleterious alleles. The south‐eastern edge of chimpanzee distribution is particularly fragmented, and conflicting hypotheses have been proposed about population connectivity and viability. To address this uncertainty, we generated both mitochondrial and MiSeq‐based microsatellite genotypes for 290 individuals ranging across western Tanzania. While shared mitochondrial haplotypes confirmed historical gene flow, our microsatellite analyses revealed two distinct clusters, suggesting two populations currently isolated from one another. However, we found evidence of high levels of gene flow maintained within each of these clusters, one of which covers an 18,000 km 2 ecosystem. Landscape genetic analyses confirmed the presence of barriers to gene flow with rivers and bare habitats highly restricting chimpanzee movement. Our study demonstrates how advances in sequencing technologies, combined with the development of landscape genetics approaches, can resolve ambiguities in the genetic history of critical populations and better inform conservation efforts of endangered species.

Observations of Multiple Young-of-the-Year to Juvenile White Sharks (Carcharodon carcharias) within South-West Australian Waters and Its Implications for a Potential Nursery Area(s) - Craig P. O’Connell; Marc Payne; Shelley Payne; Luke J. Eller; Jon Shaw; Andrew McGregor; Andre Rerekura; Madison Stewart; Andrew Fox (Journal of Marine Science and Engineering, 2023)
The white shark (Carcharodon carcharias) is a globally distributed top predator. Due to its ecological importance, increasing knowledge through continued research can enhance management measures. One such facet of biological knowledge is the identification of shark nursery areas, as protection of these regions is critical to species survival. Presently, there are two known C. carcharias nursery areas in association with the Eastern Australian subpopulation; however, a nursery area associated with the Southern-Western Australian C. carcharias subpopulation has yet to be identified. Herein, we report opportunistic laser photogrammetry, stereo-photogrammetry, and baited remote underwater video systems (BRUVS) data that resulted in the identification of sixteen young-of-the-year (YOY)-juvenile C. carcharias from two separate regions (i.e., Salisbury Island and Daw Island) in South-West Australia. Additionally, anecdotal bycatch data associated with two YOY C. carcharias (i.e., 1.40 and 1.70 m total length) from another location within the Great Australian Bight are reported. While it is premature to conclude that these sites represent discrete or an expansive interconnected nursery area, the sightings success in this study is indicative that future research may want to consider implementing a study during a similar time period (i.e., February–March) while using a similar attractant methodology (i.e., bottom-set BRUVS baited with squid [Sepioteuthis australis]) to help elucidate the unique life-history characteristics of this C. carcharias subpopulation.

Ocean acidification increases the impact of typhoons on algal communities - Callum J. Hudson; Sylvain Agostini; Shigeki Wada; Jason M. Hall-Spencer; Sean D. Connell; Ben P. Harvey (Science of The Total Environment, 2023)

Coral disease outbreak at the remote Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Michael S. Studivan; Ian C. Enochs; Adrienne M. S. Correa; Nicole Besemer; Ryan J. Eckert; Kimberly Edwards; Ryan Hannum; Xinping Hu; Marissa Nuttall; Kelly O’Connell; Ana M. Palacio-Castro; et al. (Frontiers in Marine Science, 2023)
East and West Flower Garden Bank (FGB) are part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwest Gulf of Mexico. This geographically-isolated reef system contains extensive coral communities with the highest coral cover (>50%) in the continental United States due, in part, to their remoteness and depth, and have historically exhibited low incidence of coral disease and bleaching despite ocean warming. Yet in late August 2022, disease-like lesions on seven coral species were reported during routine monitoring surveys on East and West FGB (2.1–2.6% prevalence). A series of rapid response cruises were conducted in September and October 2022 focused on 1) characterizing signs and epidemiological aspects of the disease across FGB and within long-term monitoring sites, 2) treating affected coral colonies with Base 2B plus amoxicillin, and 3) collecting baseline images through photostations and photomosaics. Marginal and/or multi-focal lesions and tissue loss were observed, often associated with substantial fish and invertebrate predation, affecting the dominant coral species Pseudodiploria strigosa (7–8% lesion prevalence), Colpophyllia natans (11–18%), and Orbicella spp. (1%). Characterizing this disease event during its early epidemic phase at East and West FGB provides a critical opportunity to observe how coral disease functions in a relatively healthy coral ecosystem versus on reefs chronically affected by various stressors (e.g., Caribbean reefs adjacent to urban centers). Insights into the etiology, spread, and impacts of the disease can ultimately inform efforts to mitigate its effects on coral communities.

Characterizing the Biological Community before and after Partial Removal of an Offshore Gas Platform in the Northwestern Gulf of Mexico - Michelle A. Johnston; Marissa F. Nuttall; Emma L. Hickerson; Kelly O’Connell; Raven D. Blakeway; John A. Embesi; Jimmy MacMillan; Douglas Peter; George P. Schmahl (Environmental Management, 2022)

Serine-Arginine Protein Kinase 1 (SRPK1): a systematic review of its multimodal role in oncogenesis - William P. Duggan; Emer O’Connell; Jochen H. M. Prehn; John P. Burke (Molecular and Cellular Biochemistry, 2022)
Alternative splicing is implicated in each of the hallmarks of cancer, and is mechanised by various splicing factors. Serine-Arginine Protein Kinase 1 (SRPK1) is an enzyme which moderates the activity of splicing factors rich in serine/arginine domains. Here we review SRPK1’s relationship with various cancers by performing a systematic review of all relevant published data. Elevated SRPK1 expression correlates with advanced disease stage and poor survival in many epithelial derived cancers. Numerous pre-clinical studies investigating a host of different tumour types; have found increased SRPK1 expression to be associated with proliferation, invasion, migration and apoptosis in vitro as well as tumour growth, tumourigenicity and metastasis in vivo. Aberrant SRPK1 expression is implicated in various signalling pathways associated with oncogenesis, a number of which, such as the PI3K/AKT, NF-КB and TGF-Beta pathway, are implicated in multiple different cancers. SRPK1-targeting micro RNAs have been identified in a number of studies and shown to have an important role in regulating SRPK1 activity. SRPK1 expression is also closely related to the response of various tumours to platinum-based chemotherapeutic agents. Future clinical applications will likely focus on the role of SRPK1 as a biomarker of treatment resistance and the potential role of its inhibition.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Evaluating the Shark Deterrent Effects of the Novel Exclusion Barrier in Comparison to the Rigorously Tested Sharksafe Barrier Technology - Craig P O’Connell; Julia Crews; Andre King; Juliet Gressle (Journal of Marine Science and Engineering, 2022)
Although exceedingly rare, shark attacks have a disproportionately large impact on human behavior, often resulting in shark culls. Due to the invasive nature of shark culls, innovating and testing non-invasive deterrent technologies that may minimize the potential for a rare negative shark encounter has become a conservation priority. One such mitigation approach is barriers, such as exclusion nets and the Sharksafe barrier. With both technologies exhibiting limitations and/or ineffectiveness (e.g., Sharksafe barrier), the development of a more effective technology was warranted. Therefore, this study had two key objectives: (1) to determine if DC 12 Volts 180 Newtons electromagnets can produce deterrent responses in the bull shark (Carcharhinus leucas) and (2) to determine if a newly designed and eco-friendly Exclusion barrier exhibits enhanced C. leucas deterrent capabilities when directly compared to the Sharksafe barrier. Based on 100 baited apparatus trials, electromagnetically treated baits resulted in significantly greater avoidance and reduced feeding frequencies. Furthermore, Poisson generalized linear mixed effect model analyses based on 27, 1-h trials illustrated that the Exclusion barrier region resulted in the greatest avoidance and lowest entrance and exit frequencies when compared to the control and Sharksafe barrier regions. Although the Exclusion barrier did not exclude all interacting sharks, the technology provided superior deterrent efficacy in relation to the Sharksafe barrier. Therefore, with many shark populations exhibiting precipitous declines, continued research on this novel technology on potentially dangerous shark species (e.g., white sharks—Carcharodon carcharias) and in varying ecological conditions (e.g., a high energy coastline) is warranted.

Genomic characterization of silvergrass cryptic virus 1, a novel partitivirus infecting Miscanthus sinensis - Larissa C. Costa; Xiaojun Hu; Martha Malapi-Wight; Mary O’Connell; Leticia M. Hendrickson; Roy S. Turner; Clint McFarland; Joseph Foster; Oscar P. Hurtado-Gonzales (Archives of Virology, 2022)

Speciation and secondary contact in a fossorial island endemic, the São Tomé caecilian - Kyle A. O’Connell; Ivan Prates; Lauren A. Scheinberg; Kevin P. Mulder; Rayna C. Bell (Molecular Ecology, 2021)
A period of isolation in allopatry typically precedes local adaptation and subsequent divergence among lineages. Alternatively, locally adapted phenotypes may arise and persist in the face of gene flow, resulting in strong correlations between ecologically‐relevant phenotypic variation and corresponding environmental gradients. Quantifying genetic, ecological, and phenotypic divergence in such lineages can provide insights into the abiotic and biotic mechanisms that structure populations and drive the accumulation of phenotypic and taxonomic diversity. Low‐vagility organisms whose distributions span ephemeral geographic barriers present the ideal evolutionary context within which to address these questions. Here, we combine genetic (mtDNA and genome‐wide SNPs) and phenotypic data to investigate the divergence history of caecilians (Amphibia: Gymnophiona) endemic to the oceanic island of São Tomé in the Gulf of Guinea archipelago. Consistent with a previous mtDNA study, we find two phenotypically and genetically distinct lineages that occur along a north‐to‐south axis with extensive admixture in the centre of the island. Demographic modelling supports divergence in allopatry (~300 kya) followed by secondary contact (~95 kya). Consequently, in contrast to a morphological study that interpreted latitudinal phenotypic variation in these caecilians as a cline within a single widespread species, our analyses suggest a history of allopatric lineage divergence and subsequent hybridization that may have blurred species boundaries. We propose that late Pleistocene volcanic activity favoured allopatric divergence between these lineages with local adaptation to climate maintaining a stable hybrid zone in the centre of São Tomé Island. Our study joins a growing number of systems demonstrating lineage divergence on volcanic islands with stark environmental transitions across small geographic distances.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Harmony on the prairie? Grassland plant and animal community responses to variation in climate across land‐use gradients - Lindsey A. Bruckerhoff; R. Kent Connell; James P. Guinnip; Elina Adhikari; Alixandra Godar; Keith B. Gido; Alice W. Boyle; Andrew G. Hope; Anthony Joern; Ellen Welti (Ecology, 2020)
Human induced climate and land‐use change are severely impacting global biodiversity, but how community composition and richness of multiple taxonomic groups change in response to local drivers and whether these responses are synchronous remains unclear. We used long‐term community‐level data from an experimentally manipulated grassland to assess the relative influence of climate and land use as drivers of community structure of four taxonomic groups: birds, mammals, grasshoppers, and plants. We also quantified the synchrony of responses among taxonomic groups across land‐use gradients and compared climatic drivers of community structure across groups. All four taxonomic groups responded strongly to land use (fire frequency and grazing), while responses to climate variability were more pronounced in grasshoppers and small mammals. Animal groups exhibited asynchronous responses across all land‐use treatments, but plant and animal groups, especially birds, exhibited synchronous responses in composition. Asynchrony was attributed to taxonomic groups responding to different components of climate variability, including both current climate conditions and lagged effects from the previous year. Data‐driven land management strategies are crucial for sustaining native biodiversity in grassland systems, but asynchronous responses of taxonomic groups to climate variability across land‐use gradients highlight a need to incorporate response heterogeneity into management planning.

Impact of Leukoaraiosis Severity on the Association of Time to Successful Reperfusion with 90-Day Functional Outcome After Large Vessel Occlusion Stroke - Abdul Ghani Mikati; Max Mandelbaum; Shweta Sapnar; Ajit S. Puri; Brian Silver; Richard P. Goddeau; Diogo C. Haussen; Majaz Moonis; Adalia H. Jun-O’Connell; Nils Henninger (Translational Stroke Research, 2020)

Assessing Nearshore Nekton Abundance, Substrate, and Environmental Conditions in the Northern Gulf of Mexico: Are There Differences Among Three Adjacent Coastal Areas and Have There Been Changes over Three Decades (1986–2015)? - Martin T. O’Connell; Mark S. Peterson; Sean P. Powers; Ann M. Uzee-O’Connell; E. John Anderson; J. Read Hendon (Estuaries and Coasts, 2019)

Towards an African Light Source - Simon H. Connell; Sekazi K. Mtingwa; Tabbetha Dobbins; Nkem Khumbah; Brian Masara; Edward P. Mitchell; Lawrence Norris; Prosper Ngabonziza; Tshepo Ntsoane; Herman Winick (Biophysical Reviews, 2019)

Potential Role of Extracellular Vesicles in the Pathophysiology of Drug Addiction - P. S. S. Rao; Kelly O’Connell; Thomas Kyle Finnerty (Molecular Neurobiology, 2018)

Eliminating Regurgitation Reduces Fibrotic Remodeling of Functional Mitral Regurgitation Conditioned Valves - Patrick S. Connell; Dragoslava P. Vekilov; Christine M. Diaz; Seulgi E. Kim; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2018)

The duality of ocean acidification as a resource and a stressor - Sean D. Connell; Zoë A. Doubleday; Nicole R. Foster; Sarah B. Hamlyn; Christopher D. G. Harley; Brian Helmuth; Brendan P. Kelaher; Ivan Nagelkerken; Kirsten L. Rodgers; Gianluca Sarà; Bayden D. Russell (Ecology, 2018)
Ecologically dominant species often define ecosystem states, but as human disturbances intensify, their subordinate counterparts increasingly displace them. We consider the duality of disturbance by examining how environmental drivers can simultaneously act as a stressor to dominant species and as a resource to subordinates. Using a model ecosystem, we demonstrate that CO 2 ‐driven interactions between species can account for such reversals in dominance; i.e., the displacement of dominants (kelp forests) by subordinates (turf algae). We established that CO 2 enrichment had a direct positive effect on productivity of turfs, but a negligible effect on kelp. CO 2 enrichment further suppressed the abundance and feeding rate of the primary grazer of turfs (sea urchins), but had an opposite effect on the minor grazer (gastropods). Thus, boosted production of subordinate producers, exacerbated by a net reduction in its consumption by primary grazers, accounts for community change (i.e., turf displacing kelp). Ecosystem collapse, therefore, is more likely when resource enrichment alters competitive dominance of producers, and consumers fail to compensate. By recognizing such duality in the responses of interacting species to disturbance, which may stabilize or exacerbate change, we can begin to understand how intensifying human disturbances determine whether or not ecosystems undergo phase shifts.

Kaiso is highly expressed in TNBC tissues of women of African ancestry compared to Caucasian women - Blessing I. Bassey-Archibong; Shawn M. Hercules; Lyndsay G. A. Rayner; Desiree H. A. Skeete; Suzanne P. Smith Connell; Ian Brain; Adetola Daramola; Adekunbiola A. F. Banjo; Jung S. Byun; Kevin Gardner; Jonathan Dushoff; Juliet M. Daniel (Cancer Causes & Control, 2017)

ADAR RNA editing in human disease; more to it than meets the I - Angela Gallo; Dragana Vukic; David Michalík; Mary A. O’Connell; Liam P. Keegan (Human Genetics, 2017)

Application of Species Distribution Models to Identify Estuarine Hot Spots for Juvenile Nekton - Ann Commagere Hijuelos; Shaye E. Sable; Ann M. O’Connell; James P. Geaghan; David C. Lindquist; Eric D. White (Estuaries and Coasts, 2017)

Impact of early prehistoric farming on chironomid communities in northwest Ireland - Karen J. Taylor; Aaron P. Potito; David W. Beilman; Beatrice Ghilardi; Michael O’Connell (Journal of Paleolimnology, 2017)

Climate‐driven disparities among ecological interactions threaten kelp forest persistence - Euan J. Provost; Brendan P. Kelaher; Symon A. Dworjanyn; Bayden D. Russell; Sean D. Connell; Giulia Ghedini; Bronwyn M. Gillanders; WillIAM Figueira; Melinda A. Coleman (Global Change Biology, 2017)
The combination of ocean warming and acidification brings an uncertain future to kelp forests that occupy the warmest parts of their range. These forests are not only subject to the direct negative effects of ocean climate change, but also to a combination of unknown indirect effects associated with changing ecological landscapes. Here, we used mesocosm experiments to test the direct effects of ocean warming and acidification on kelp biomass and photosynthetic health, as well as climate‐driven disparities in indirect effects involving key consumers (urchins and rock lobsters) and competitors (algal turf). Elevated water temperature directly reduced kelp biomass, while their turf‐forming competitors expanded in response to ocean acidification and declining kelp canopy. Elevated temperatures also increased growth of urchins and, concurrently, the rate at which they thinned kelp canopy. Rock lobsters, which are renowned for keeping urchin populations in check, indirectly intensified negative pressures on kelp by reducing their consumption of urchins in response to elevated temperature. Overall, these results suggest that kelp forests situated towards the low‐latitude margins of their distribution will need to adapt to ocean warming in order to persist in the future. What is less certain is how such adaptation in kelps can occur in the face of intensifying consumptive (via ocean warming) and competitive (via ocean acidification) pressures that affect key ecological interactions associated with their persistence. If such indirect effects counter adaptation to changing climate, they may erode the stability of kelp forests and increase the probability of regime shifts from complex habitat‐forming species to more simple habitats dominated by algal turfs.

A minimally invasive technique to assess several life‐history characteristics of the endangered great hammerhead shark Sphyrna mokarran - C. P. O'Connell; G. Leurs (Journal of Fish Biology, 2016)
A dorsal‐fin photo‐identification technique paired with a non‐invasive parallel laser photogrammetry technique was used to non‐invasively identify individual Sphyrna mokarran over time. Based on the data collected over a duration of 59 days, 16 different S. mokarran (mean ± s.d . pre‐caudal length: 220·82 ± 13·66 cm; mean ± s.d . cephalofoil width: 71·38 ± 7·94 cm) were identified using dorsal‐fin photo‐identification, with a mean ± s.d . shark re‐sighting frequency of 4·05 ± 3·06 at‐sea days. The results illustrate a high S. mokarran sighting rate and therefore, the utilization of parallel laser photogrammetry and dorsal‐fin photo‐identification may be a plausible multi‐year approach to aid in non‐invasively determining the growth rate and inter‐annual site fidelity of these animals.

Risks and advantages of using surface laser photogrammetry on free‐ranging marine organisms: a case study on white sharks Carcharodon carcharias - G. Leurs; C. P. O'Connell; S. Andreotti; M. Rutzen; H. Vonk Noordegraaf (Journal of Fish Biology, 2015)
This study employed a non‐lethal measurement tool, which combined an existing photo‐identification technique with a surface, parallel laser photogrammetry technique, to accurately estimate the size of free‐ranging white sharks Carcharodon carcharias . Findings confirmed the hypothesis that surface laser photogrammetry is more accurate than crew‐based estimations that utilized a shark cage of known size as a reference tool. Furthermore, field implementation also revealed that the photographer's angle of reference and the shark's body curvature could greatly influence technique accuracy, exposing two limitations. The findings showed minor inconsistencies with previous studies that examined pre‐caudal to total length ratios of dead specimens. This study suggests that surface laser photogrammetry can successfully increase length estimation accuracy and illustrates the potential utility of this technique for growth and stock assessments on free‐ranging marine organisms, which will lead to an improvement of the adaptive management of the species.

Ocean acidification through the lens of ecological theory - Brian Gaylord; Kristy J. Kroeker; Jennifer M. Sunday; Kathryn M. Anderson; James P. Barry; Norah E. Brown; Sean D Connell; Sam Dupont; Katharina E. Fabricius; Jason M. Hall-Spencer; Terrie Klinger; Marco Milazzo; et al. (Ecology, 2015)
Ocean acidification, chemical changes to the carbonate system of seawater, is emerging as a key environmental challenge accompanying global warming and other human‐induced perturbations. Considerable research seeks to define the scope and character of potential outcomes from this phenomenon, but a crucial impediment persists. Ecological theory, despite its power and utility, has been only peripherally applied to the problem. Here we sketch in broad strokes several areas where fundamental principles of ecology have the capacity to generate insight into ocean acidification's consequences. We focus on conceptual models that, when considered in the context of acidification, yield explicit predictions regarding a spectrum of population‐ and community‐level effects, from narrowing of species ranges and shifts in patterns of demographic connectivity, to modified consumer–resource relationships, to ascendance of weedy taxa and loss of species diversity. Although our coverage represents only a small fraction of the breadth of possible insights achievable from the application of theory, our hope is that this initial foray will spur expanded efforts to blend experiments with theoretical approaches. The result promises to be a deeper and more nuanced understanding of ocean acidification and the ecological changes it portends.

Recommended guiding principles for reporting on camera trapping research - P. D. Meek; G. Ballard; A. Claridge; R. Kays; K. Moseby; T. O’Brien; A. O’Connell; J. Sanderson; D. E. Swann; M. Tobler; S. Townsend (Biodiversity and Conservation, 2014)

Mature male parr contribution to the effective size of an anadromous A tlantic salmon ( S almo salar ) population over 30 years - Devon L. Johnstone; Michael F. O'Connell; Friso P. Palstra; Daniel E. Ruzzante (Molecular Ecology, 2013)
We describe temporal changes in the genetic composition of a small anadromous A tlantic salmon ( S almo salar ) population from South Newfoundland, an area where salmon populations are considered threatened ( COSEWIC 2010). We examined the genetic variability (13 microsatellite loci) in 869 out‐migrating smolt and post‐spawning kelt samples, collected from 1985 to 2011 for a total of 22 annual collections and a 30 year span of assigned cohorts. We estimated the annual effective number of breeders ( N b ) and the generational effective population size ( N e ) through genetic methods and demographically using the adult sex ratio. Comparisons between genetic and demographic estimates show that the adult spawners inadequately explain the observed N e estimates, suggesting that mature male parr are significantly increasing N b and N e over the study period. Spawning as parr appears to be a viable and important strategy in the near absence of adult males.

Preformulation Study of NSC-726796 - Duoli Guo; James P. Cain; Sean O’Connell; Erin R. Gardner; Steven Pisle; William D. Figg; S. Esmail Tabibi; Samuel H. Yalkowsky (AAPS PharmSciTech, 2012)

Reducing per capita food supply alters urchin condition and habitat - Juan P. Livore; Sean D. Connell (Marine Biology, 2012)

Variation in wind and piscivorous predator fields affecting the survival of Atlantic salmon, Salmo salar , in the Gulf of Maine - K. D. FRIEDLAND; J. P. MANNING; J. S. LINK; J. R. GILBERT; A. T. GILBERT; A. F. O’CONNELL (Fisheries Management and Ecology, 2012)
Observations relevant to the North American stock complex of Atlantic salmon, Salmo salar L., suggest that marine mortality is influenced by variation in predation pressure affecting post‐smolts during the first months at sea. This hypothesis was tested for Gulf of Maine (GOM) stocks by examining wind pseudostress and the distribution of piscivorous predator fields potentially affecting post‐smolts. Marine survival has declined over recent decades with a change in the direction of spring winds, which is likely extending the migration of post‐smolts by favouring routes using the western GOM. In addition to changes in spring wind patterns, higher spring sea surface temperatures have been associated with shifting distributions of a range of fish species. The abundance of several pelagic piscivores, which based on their feeding habits may predate on salmon post‐smolts, has increased in the areas that serve as migration corridors for post‐smolts. In particular, populations of silver hake, Merluccius bilinearis (Mitchell), red hake, Urophycis chuss (Walbaum), and spiny dogfish, Squalus acanthias L., increased in size in the portion of the GOM used by post‐smolts. Climate variation and shifting predator distributions in the GOM are consistent with the predator hypothesis of recruitment control suggested for the stock complex.

A review and tests of hypotheses about causes of the KwaZulu-Natal sardine run - P Fréon; J C Coetzee; C D van der Lingen; A D Connell; S H O’Donoghue; M J Roberts; H Demarcq; C G Attwood; S J Lamberth; L Hutchings (African Journal of Marine Science, 2010)

Evidence of selection for resistance to paralytic shellfish toxins during the early life history of soft‐shell clam, Mya arenaria , populations - V. M. Bricelj; S. P. MacQuarrie; J. A. E. Doane; L. B. Connell (Limnology and Oceanography, 2010)
This study identifies early, postmetamorphic soft‐shell clams, Mya arenaria , as the life‐history stage most susceptible to effects of blooms of paralytic shellfish poisoning (PSP) toxin–producing Alexandrium spp. Laboratory experiments used progeny from predominantly susceptible (naϊve) or resistant (annually exposed) NW Atlantic populations. Growth and survival of toxified veliger larvae did not differ from those fed nontoxic algae. In contrast, postlarvae (4–12‐mm shell length) from both populations exposed to a highly toxic Alexandrium tamarense isolate (~ 100 cells mL −1 , 64–69 pg saxitoxin equivalents [STXeq] cell −1 ) suffered burrowing incapacitation, toxin accumulation, and mortalities within 1 week of toxin exposure. These effects were greater and occurred sooner in the naϊve population. Short‐term toxification in the laboratory caused a significant shift in the genotypic composition of this population, determined with a molecular marker for sodium‐channel resistance. Clams with the sensitive genotype were selectively eliminated relative to resistant or heterozygote clams. Ingestion of toxic cells (too large for larval capture) is thus required to elicit toxic effects. Exposure to mixed, toxic, and nontoxic algal suspensions demonstrated that adverse effects to fitness (survival and growth) were dose‐dependent, occurring only at ≥ 50 cells mL −1 of the isolate used (PR18b). Paralysis and thus increased predatory risk occurred even at 10 cells mL −1 . Postlarvae M. arenaria , were more susceptible to PSP than large (> 30 mm) juveniles. Natural selection for resistance in Atlantic populations will thus vary latitudinally with the timing, duration, and intensity of toxic blooms.

Stability of 5-Fluoro-2′-deoxycytidine and Tetrahydrouridine in Combination - Duoli Guo; Paul B. Myrdal; Kelly L. Karlage; Sean P. O’Connell; Travis J. Wissinger; S. Esmail Tabibi; Samuel H. Yalkowsky (AAPS PharmSciTech, 2010)

Marine Isotope Stage 7–6 transition age for beach sediments at Morston, north Norfolk, UK: implications for Pleistocene chronology, stratigraphy and tectonics - P. G. Hoare; S. J. Gale; R. A. J. Robinson; E. R. Connell; N. R. Larkin (Journal of Quaternary Science, 2009)
Optically stimulated luminescence age estimates for the Pleistocene beach at Morston, north Norfolk, UK, obtained by the single‐aliquot regenerative‐dose protocol, indicate a Marine Isotope Stage (MIS) 7–6 transition date. The view that the beach is of Ipswichian (MIS 5e) age, held virtually unanimously for the last 75 years, may now be discarded. The extant beach sequence lies up to ∼5 m OD, yet global models suggest that MIS 7–6 sea levels were typically substantially below that of today. The explanation may lie with poorly understood regional tectonic movements. The MIS 7–6 date helps to constrain the ages of glacial deposits that bracket the beach sediments at Morston. The underlying Marly Drift till cannot be younger than MIS 8; this may also be true for the complex assemblage of glaciogenic landforms and sediments, including the Blakeney esker, in the adjacent lower Glaven valley. The well‐established Late Devensian (MIS 2) age of the Hunstanton Till is not compromised by the date of the Morston beach. There is no indication of a proposed Briton's Lane glaciation during MIS 6 times. Copyright © 2009 John Wiley & Sons, Ltd.

Analysis of the coding regions of VEGFR3 and VEGFC in Milroy disease and other primary lymphoedemas - F. C. Connell; P. Ostergaard; C. Carver; G. Brice; N. Williams; S. Mansour; P. S. Mortimer; Steve Jeffery (Human Genetics, 2009)

Recombinant protein production in insect larvae: host choice, tissue distribution, and heterologous gene instability - Elena S. Kovaleva; Kevin P. O’Connell; Patricia Buckley; Zhi Liu; David C. Davis (Biotechnology Letters, 2009)

Community‐level density dependence: an example from a shallow coral assemblage - Jason E. Tanner; Terence P. Hughes; Joseph H. Connell (Ecology, 2009)
While density dependence is a popular topic of research in population ecology, it has received much less attention at the community level. Using 27 years of data from Heron Island, on Australia's Great Barrier Reef, we develop a matrix model of coral community dynamics that shows that community‐level density dependence does occur and that it is fairly common, being found in 38% of the model parameters for which it was tested. In particular, colonization of free space (through either recruitment or growth of existing colonies) was nearly always density dependent. There were no consistent patterns in the results for mortality, persistence, or species interactions. Most transitions were found to be dependent on the cover of the incoming species group, with only a few dependent on that of the outgoing species group. In addition, few of the transitions representing species interactions were dependent on the amount of free space present, suggesting that the cover of other species does not influence encounters. When these results were combined into a model of community dynamics, it was found that density dependence resulted in a moderate increase in coral cover, which was spread over most species groups. The dynamics of the density‐dependent assemblage were also a lot noisier than those of an assemblage without density dependence. Sensitivity analysis indicated that it was density dependence in the colonization probabilities, particularly of encrusting acroporids, bushy Acropora and staghorn Acropora , which had the main influence on the model, although persistence of free space was also important. Transitions representing mortality were only of minor importance, and those representing species interactions were of no importance.

Analysis of the coding regions of VEGFR3 and VEGFC in Milroy disease and other primary lymphoedemas - F. C. Connell; P. Ostergaard; C. Carver; G. Brice; N. Williams; S. Mansour; P. S. Mortimer; Steve Jeffery (Human Genetics, 2009)

Genetic divergence between sympatric Arctic charr Salvelinus alpinus morphs in Gander Lake, Newfoundland: roles of migration, mutation and unequal effective population sizes - D. Gomez‐Uchida; K. P. Dunphy; M. F. O’Connell; D. E. Ruzzante (Journal of Fish Biology, 2008)
A suite of 10 microsatellite loci was used to examine genetic divergence between two sympatric morphs of Arctic charr Salvelinus alpinus (‘dark’ and ‘pale’) inhabiting Gander Lake, Newfoundland. Results can be summarized as follows: (1) the morphs are strongly reproductively isolated – gene flow–migration estimates were consistently low in long and short‐term evolutionary timescales of analysis; (2) intermorph divergence based on allele size ( R ST ) was significantly larger than those based on allele state ( θ ) implying a cumulative effect of stepwise‐like mutations; (3) historical (coalescent) and current (linkage disequilibrium) point estimates of effective population size ( N e ) were consistently higher for dark than for pale S. alpinus . The first and second findings lend support to the hypothesis that divergence between forms may have preceded the last glacial period (ending c. 12 000 years bp ). The third finding argues for significant differences in habitat quantity and quality between morphs, which were emphasized in a previous study. Overall, these analyses underscore the importance of genetic assessment and monitoring in the conservation of fish diversity, with emphasis on ‘rare’ or under‐represented forms among temperate species pairs.

Carbon allocation in boreal black spruce forests across regions varying in soil temperature and precipitation - JASON G. VOGEL; BEN P. BOND‐LAMBERTY; EDWARD A. G. SCHUUR; STITH T. GOWER; MICHELLE C. MACK; KARI E. B. O'CONNELL; DAVID W. VALENTINE; ROGER W. RUESS (Global Change Biology, 2008)
A common hypothesis for northern ecosystems is that low soil temperatures inhibit plant productivity. To address this hypothesis, we reviewed how separate components of ecosystem carbon (C) cycling varied along a soil temperature gradient for nine well‐drained, relatively productive boreal black spruce ( Picea mariana Mill. [B.S.P.]) forests in Alaska, USA, and Saskatchewan and Manitoba, Canada. Annual soil temperature [expressed as soil summed degree days (SDD)] was positively correlated with aboveground net primary productivity (ANPP), while negatively correlated with total belowground carbon flux (TBCF). The partitioning of C to ANPP at the expense of root processes represented a nearly 1 : 1 tradeoff across the soil temperature gradient, which implied that the amount of C cycling through these black spruce ecosystems was relatively insensitive to variation in SDD. Moreover, the rate at which C accumulated in the ecosystem since the last stand replacing fire was unrelated to SDD, but SDD was positively correlated to the ratio of spruce‐biomass : forest‐floor‐mass. Thus, plant partitioning of C and the distribution of ecosystem C were apparently affected by soil temperature, although across regions, precipitation co‐varied with soil temperature. These two factors likely correlated with one another because of precipitation's influence on soil heat balance, suggesting that a soil temperature–precipitation interaction could be responsible for the shifts in C allocation. Nonetheless, our results highlight that for this boreal ecosystem, ANPP and TBCF can be negatively correlated. In tropical and temperate forests, TBCF and ANPP have been reported as positively correlated, and our results may reflect the unique interactions between soil temperature, forest floor accumulation, rooting depth, and nutrient availability that characterize the black spruce forest type.

Complexity in the relationship between matrix composition and inter-patch distance in fragmented habitats - P. J. Goodsell; S. D. Connell (Marine Biology, 2008)

Population structure and gene flow reversals in Atlantic salmon ( Salmo salar ) over contemporary and long‐term temporal scales: effects of population size and life history - FRISO P. PALSTRA; MICHAEL F. O’CONNELL; DANIEL E. RUZZANTE (Molecular Ecology, 2007)
Metapopulation dynamics are increasingly invoked in management and conservation of endangered species. In this context, asymmetrical gene flow patterns can be density dependent, with migration occurring mainly from larger into smaller populations, which may depend on it for their persistence. Using genetic markers, such patterns have recently been documented for various organisms including salmonids, suggesting this may be a more general pattern. However, metapopulation theory does not restrict gene flow asymmetry to ‘source‐sink’ structures, nor need these patterns be constant over longer evolutionary timescales. In anadromous salmonids, gene flow can be expected to be shaped by various selective pressures underlying homing and dispersal (‘straying’) behaviours. The relative importance of these selective forces will vary spatially and for populations of different census size. Furthermore, the consequences of life‐history variation among populations for dispersal and hence gene flow remain poorly quantified. We examine population structure and connectivity in Atlantic salmon ( Salmo salar L.) from Newfoundland and Labrador, a region where populations of this species are relatively pristine. Using genetic variation at 13 microsatellite loci from samples ( N = 1346) collected from a total of 20 rivers, we examine connectivity at several regional and temporal scales and test the hypothesis that the predominant direction of gene flow is from large into small populations. We reject this hypothesis and find that the directionality of migration is affected by the temporal scale over which gene flow is assessed. Whereas large populations tend to function as sources of dispersal over contemporary timescales, such patterns are often changed and even reversed over evolutionary, coalescent‐derived timescales. These patterns of population structure furthermore vary between different regions and are compatible with demographic and life‐history attributes. We find no evidence for sex‐biased dispersal underlying gene flow asymmetry. Our findings caution against generalizations concerning the directionality of gene flow in Atlantic salmon and emphasize the need for detailed regional study, if such information is to be meaningfully applied in conservation and management of salmonids.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Bermuda subtropical storms - M. P. Guishard; E. A. Nelson; J. L. Evans; R. E. Hart; D. G. O’Connell (Meteorology and Atmospheric Physics, 2007)

Evaluation of the IDI-MRSA assay on the SmartCycler real-time PCR platform for rapid detection of MRSA from screening specimens - A. S. Rossney; C. M. Herra; M. M. Fitzgibbon; P. M. Morgan; M. J. Lawrence; B. O’Connell (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Real-time fluorogenic PCR assays for the detection of entA, the gene encoding staphylococcal enterotoxin A - Jennifer R. Horsmon; Cheng J. Cao; Akbar S. Khan; Mark V. Gostomski; James J. Valdes; Kevin P. O’Connell (Biotechnology Letters, 2007)

Population differences in nerve resistance to paralytic shellfish toxins in softshell clam, Mya arenaria, associated with sodium channel mutations - Laurie B. Connell; Scott P. MacQuarrie; Betty M. Twarog; Melissa Iszard; V. Monica Bricelj (Marine Biology, 2007)

Real-time Fluorogenic PCR Assays for the Detection of entA, the Gene Encoding Staphylococcal Enterotoxin A - Jennifer R. Horsmon; Cheng J. Cao; Akbar S. Khan; Mark V. Gostomski; James J. Valdes; Kevin P. O'Connell (Biotechnology Letters, 2006)

Response of fishes to floodplain connectivity during and following a 500-year flood event in the unimpounded upper Mississippi River - Valerie A. Barko; David P. Herzog; Martin T. O’Connell (Wetlands, 2006)

Epidemiological typing of MRSA isolates from blood cultures taken in Irish hospitals participating in the European Antimicrobial Resistance Surveillance System (1999–2003) - A. S. Rossney; M. J. Lawrence; P. M. Morgan; M. M. Fitzgibbon; A. Shore; D. C. Coleman; C. T. Keane; B. O’Connell (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Environmentally-Sensitive Water Resources Planning - M. A. Yurdusev; P. E. O'connell (Water Resources Management, 2005)

Environmentally-Sensitive Water-Resources Planning: - M. A. Yurdusev; P. E. O'Connell (Water Resources Management, 2005)

Estimating Regional Variation in Cancer Survival: A Tool for Improving Cancer Care - Xue Q. Yu; Dianne L. O'Connell; Robert W. Gibberd; David P. Smith; Paul W. Dickman; Bruce K. Armstrong (Cancer Causes & Control, 2004)

Contribution of decomposing harvest residues to nutrient cycling in a second rotation Eucalyptus globulus plantation in south-western Australia - P. Damon; S. J. Rance; K. Shammas; A. M. O'Connell; T. S. Grove; R. McMurtrie (Biology and Fertility of Soils, 2003)

Cotton α-Globulin Promoter: Isolation and Functional Characterization in Transgenic Cotton, Arabidopsis, and Tobacco - Ganesan Sunilkumar; James P. Connell; C. W. Smith; Avutu S. Reddy; Keerti S. Rathore (Transgenic Research, 2002)

An Interactive Management System for Operational Control of Kirazdere Reservoir (Turkey) - Z. Rao; I. N. Moore; P. E. O’Connell; D. G. Jamieson (Water Resources Management, 2001)

Effect of cultivar, row spacing, and weed management on weed biomass, potato yield, and net crop value - Shawn P. Conley; Larry K. Binning; Timothy R. Connell (American Journal of Potato Research, 2001)

Isolation and characterization of the Δ12-fatty acid desaturase in peanut (Arachis hypogaea L.) and search for polymorphisms for the high oleate trait in Spanish market-type lines - Y. López; H. L. Nadaf; O. D. Smith; J. P. Connell; A. S. Reddy; A. K. Fritz (Theoretical and Applied Genetics, 2000)

Role of Bacterial Virulence Factors and Host Factors in the Outcome of Escherichia coli Bacteraemia - T. A. M. Hekker; A. B. J. Groeneveld; A. M. Simoons-Smit; P. de Man; H. Connell; D. M. MacLaren (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Cultivar Resistance to Anthracnose Disease of Cowpea (Vigna unguiculata (L.) Walp.) caused by Colletotrichum destructivum O'Gara - A.O. Latunde-Dada; R.J. O'Connell; P. Bowyer; J.A. Lucas (European Journal of Plant Pathology, 1999)

Gene expression patterns in cell lines from patients with 18q- syndrome - Zhiqiang Wang; Jannine D. Cody; Robin J. Leach; P. O'Connell (Human Genetics, 1999)

Multiple stressors on coral reefs: A long ‐term perspective - T. P. Hughes; J. H. Connell (Limnology and Oceanography, 1999)
Coral reefs are subject to a high frequency of recurrent biological and physical disturbances. The temporal and spatial scales of these are often large and difficult to study, so that most of our knowledge of disturbances on coral reefs comes from investigations conducted at one or a few sites, over short periods of time. We argue that studying single events in isolation can be misleading and that a longer term approach is necessary for understanding the responses of coral reef assemblages to multiple stressors. We present first a brief review of the impacts of physical disturbance (e.g., cyclones, hurricanes) on the community dynamics of coral reefs, with special attention to the effects of recurrent events. We then examine two unusually detailed, long ‐term data sets from Heron Island, Australia, and Jamaica which demonstrate some of the complexities of multiple stressors (broadly defined as natural or man‐made disturbances).

A High Through-put Procedure for Capturing Microsatellites from Complex Plant Genomes - James P. Connell; Sujata Pammi; Muhammad J. Iqbal; Tim Huizinga; Avutu S. Reddy (Plant Molecular Biology Reporter, 1998)

Variant in sulfonylurea receptor-1 gene is associated with high insulin concentrations in non-diabetic Mexican Americans: SUR-1 gene variant and hyperinsulinemia - Denise L. Goksel; Kathryn Fischbach; Ravindranath Duggirala; Braxton D. Mitchell; Lydia Aguilar-Bryan; John Blangero; M. P. Stern; Peter O’Connell (Human Genetics, 1998)

Genetic structuring among Alaskan Pacific herring populations identified using microsatellite variation - M. O'Connell; M. C. Dillon; J. M. Wright; P. Bentzen; S. Merkouris; J. Seeb (Journal of Fish Biology, 1998)
Five highly variable microsatellite loci were used to investigate population structuring in Pacific herring Clupea pallasi collected from Kodiak Island, two sites in the Bering Sea and four sites within Prince William Sound, Alaska. All loci revealed high levels of variability with heterozygosity estimates ranging from 86 to 97% (mean heterozygosity: 89%). The variation was structured significantly among sites suggesting that the samples investigated were genetically distinct from each other. Genetic divergence was greatest between populations from the Bering Sea and those from Prince William Sound. The Kodiak Island and Point Chalmers samples appeared to be distinct from the Prince William Sound and Bering Sea populations. The observed genetic distance relationships among samples could be explained largely in terms of geographical separation.

Towards a Regional Index of Biological Integrity: the Example of Forested Riparian Ecosystems - Robert P. Brooks; Timothy J. O'Connell; Denice H. Wardrop; Laura E. Jackson (Environmental Monitoring and Assessment, 1998)

A Bird Community Index of Biotic Integrity for the Mid-Atlantic Highlands - T.J. O'Connell; L. E. Jackson; R. P. Brooks (Environmental Monitoring and Assessment, 1998)

Predicting rainfall statistics in England and Wales using atmospheric circulation variables - C. G. Kilsby; P. S. P. Cowpertwait; P. E. O'Connell; P. D. Jones (International Journal of Climatology, 1998)

In vivo effects on striatal dopamine D 2 receptor binding by the novel atypical antipsychotic drug sertindole - a 123 I IBZM single photon emission tomography (SPET) study - L. S. Pilowsky; P. O'Connell; N. Davies; G. F. Busatto; D. C. Costa; R. M. Murray; P. J. Ell; R. W. Kerwin (Psychopharmacology, 1997)

The H8 antigen of pathogenic Neisseriae - J. P. Woods; E. L. Aho; D. S. Barritt; J. R. Black; T. D. Connell; T. H. Kawula; S. M. Spinola; J. G. Cannon (Antonie van Leeuwenhoek, 1987)